The Legislative Basis for Resolving the Conflict of Interests in the Civil Service in the Russian Federation and Foreign Countries - ILAEVA, Zarema M.; ALIKHADZHIEVA, Diana S.; BEKSULTANOVA, Aibikal (Journal of Advanced Research in Law and Economics; Vol 9 No 3(33) (2018): JARLE, Volume IX, Issue 3(33), Summer 2018, 2018)
The object of the article -’conflict of interests’ - is quite new for the Russian Federation, therefore it is necessary to study the works of the Russian and foreign authors, as well as the Russian and foreign legislation. The purpose of the study is to identify the patterns of emergence and development of situations of conflict of interests in the performance of civil servants and to identify ways to improve mechanisms that can resolve conflicts of interest in public service. Thus, it is necessary to make a comprehensive analysis of such a phenomenon as a conflict of interests in the system of functioning of the civil service, to understand how deep this problem is for Russia's statehood, and to explore mechanisms that will help resolve conflicts of interest in the work of the civil service. The research indicates that the institute for conflict of interests settlement in Russian Federation needs further improvement through different mechanisms and measurements that will increase transparency, efficiency of decision making by the officials and reducing the level of corruption in Russian Federation. Therefore, the results of the research and the analysis of Russian legislation confirms that settlement mechanism is a problematic area due to its shortcomings in the system of preventing and resolving conflicts of interests